The Effect of Airport Road Access Design on Senior Drivers’ Wayfinding - Anuar, Nur Khairiel; Sabar, Rohafiz; Melan, Mustakim (International Journal of Supply Chain Management, 2020)
The purpose of this study was to evaluate the impact of airport road access wayfinding and signage preferences on senior driver. Wayfinding complexity varied due to differing levels of airport road-side furniture such as traffic signs and bollards. Experienced car drivers were asked to drive self-designed simulated routes. Forty drivers in the age ranges: 50 to over 60 were selected to perform the study. Questionnaire then were distributed after driving simulation test was performed. The driver performance was analysed by Mean and Standard Deviation (SD), and discussed with reference to the use of the driving simulator and drivers’ general experience. The results confirmed that there is a correlation between airport road access wayfinding design and senior driving performance.